Analisis Faktor yang Berhubungan dengan Kepatuhan Fisioterapi Pasien Pasca Stroke di RS Bethesda Yogyakarta - Siti Fadlilah; Fransiska Lanni; Romadhani Tri Purnomo (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2019)
Disability is one of the most common effects of stroke. To avoid the possibility of occurrence of post-stroke problems, rehabilitation efforts are needed continuously. Physiotherapy is an effort to restore function and movement in post-stroke patients. Achievement of recovery depends on compliance with physiotherapy and body condition. To determine the relationship of age, sex, education, and knowledge with adherence to physiotherapy schedule for post-stroke patients at the Bethesda Hospital Medical Rehabilitation Unit, Yogyakarta. The design of this study was cross sectional with the sampling technique used was quota sampling. The sample in this study was post-stroke patients who received a schedule for undergoing physiotherapy at the Medical Rehabilitation Unit of Bethesda Hospital Yogyakarta with a total of 54 respondents. Bivariate analysis used Kendal Tau. The highest number of respondents in the final elderly category was 24 respondents (44.4%). The majority of men are 38 respondents (70.4%). The education level of the respondents is the level of primary education (33.3%), middle (33.3%), and high (33.3%). The level of knowledge of the respondents in most categories is enough, namely 27 respondents (50%). Most of the respondents included in the category adhere to physiotherapy schedules (50.0%). Bivariate test results between age, sex, level of education, and knowledge with adherence to the physiotherapy schedule of post-stroke patients obtained a P-value of 0.003; 0.025; 0.463; and 0.017. There is a relationship between age, sex, and education with adherence to physiotherapy schedule of post-stroke patients at the Bethesda Hospital Medical Rehabilitation Unit in Yogyakarta. While knowledge does not have a significant relationship with the compliance of physiotherapy schedules of post-stroke patients at the Bethesda Hospital Medical Rehabilitation Unit in Yogyakarta.